Numerical Analysis of Ground Motion Effects in the Loess Regions of Western China - Tuo Chen; Wei Ma; Jianzhou Wang (Shock and Vibration)
Loess is widely distributed in the western part of China and its area comprises 6.6% of Chinese territory. Because of the characteristics of high porosity, low strength, and weak cementation, the loess is characterized by high seismic vulnerability which has been observed and confirmed by many researchers at home and abroad. The postquake field investigation and the laboratory study have shown that the ground motion effects, including the amplification effects and slope effects, were obvious in loess sites. Moreover, the causes of landslides, seismic subsidence, and liquefaction were mainly attributed to this special soil structure and properties. In this paper, based on the data of shear wave velocity of typical loess in Lanzhou region, combining the results of dynamic triaxial tests, the numerical analysis of ground motion effects in the loess regions is analyzed. The results reveal how the ground motion effects are checked and demonstrated the important role of numerical simulations while studying the characteristics of ground motions.